2008
DOI: 10.1371/journal.pgen.1000253
|View full text |Cite
|
Sign up to set email alerts
|

p8/TTDA Overexpression Enhances UV-Irradiation Resistance and Suppresses TFIIH Mutations in a Drosophila Trichothiodystrophy Model

Abstract: Mutations in certain subunits of the DNA repair/transcription factor complex TFIIH are linked to the human syndromes xeroderma pigmentosum (XP), Cockayne's syndrome (CS), and trichothiodystrophy (TTD). One of these subunits, p8/TTDA, interacts with p52 and XPD and is important in maintaining TFIIH stability. Drosophila mutants in the p52 (Dmp52) subunit exhibit phenotypic defects similar to those observed in TTD patients with defects in p8/TTDA and XPD, including reduced levels of TFIIH. Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…3E). We previously observed that the kinetics of CPD removal in third instar larvae can be detected 4 h after irradiation and occurs faster than in mammalian cells (32). Interestingly, the H3K9me3 demethylated state is maintained in heterochromatin for several hours until the H3K9me3 levels rise again (supplemental Fig.…”
Section: Ep-kdm4bmentioning
confidence: 90%
“…3E). We previously observed that the kinetics of CPD removal in third instar larvae can be detected 4 h after irradiation and occurs faster than in mammalian cells (32). Interestingly, the H3K9me3 demethylated state is maintained in heterochromatin for several hours until the H3K9me3 levels rise again (supplemental Fig.…”
Section: Ep-kdm4bmentioning
confidence: 90%
“…Interaction between p52 and p8/TTDA further strengthens the anchoring of TFIIH to DNA after a genotoxic attack (107). Interestingly, overexpression of p8/TTDA in p52-deficient Drosophila cells exhibiting a TTD phenotype or in human XPD-deficient cells abrogates their strong UV-sensitive phenotypes (108).…”
Section: Regulation Of Xpb and Xpd Activities During Nermentioning
confidence: 97%
“…In addition, overexpression of Dmp8 generates flies that are more resistant to UV irradiation (12). In this study, we report that the Dmp8 gene is encoded in a bicistronic transcript along with the fly homolog of the Swc6/p18…”
mentioning
confidence: 78%
“…4B) suggests that the phenotypes observed in these flies are primarily due to the absence of Dmp8. To confirm this, we constructed transgenic flies that expressed either Dmp8 fused to a six-histidine tag (12) or Dmp18 containing the Myc epitope (see "Experimental Procedures"). These flies were crossed with the l(2)SH1279 flies to generate organisms that were homozygous for the l(2)SH1279 insertion with one or two copies of the transgene.…”
Section: The Dmp8 Subunit Of Tfiih Is Encoded As a Bicistronic Transcmentioning
confidence: 99%
See 1 more Smart Citation